ANALISIS TARIKAN PERJALANAN PADA PERBELANJAAN RAMAYANA MALL DI KOTA BONTANG - SAFAR, IRWAN DESPIADI (KURVA S JURNAL MAHASISWA, 2017)
Ramayana mall is one of the busiest areas in Bontang city which is close to Pasar rawa indah (traditional market). Many buildings in that region have a great has a great influence on the pull of travel in the region, a trip to ramayana Mall that need to be analyzed on the journey toward the pull model to the region.Â This study aims to explain the model of trip attraction in ramayana mall and to determine the percentage of R2 and F, which is expected to be used for estimate the quantity of trip attraction.Primary data obtained by questioner carried out with random sampling, while secondary data obtained by independent data of ramayana Mall, that is width, total of employees, and all of the supporting facilities and the dependent variable is the quantity of trip attraction.Results of the analysis model of the pull of total trips to the shape modeling Y=0,524+0,110X2+0,196X3+0,306X5 with the percentage of R2= 0,545. It showed the context level of dependent variable and independent variable on High Colleration means 54,5%. Percentage of total trip attraction can be explain by variable Y = total trip attraction, X1 = age, X3 = education and Â X5 = salary and the percentage of F (percentage F > table F) (27,590>2,65).